EFEKTIVITAS PERLINDUNGAN ANAK TERHADAP ANAK SEBAGAI KORBAN PROSTITUSI ONLINE DALAM KASUS DI MADIUN - Salsabila Sutardja, Putri; Adea Rohma, Dewinta; Oktavianti, Lisa (DiH: Jurnal Ilmu Hukum, 2021)
AbstractChildren are agents of change where children must be nurtured and protected for their physical and mental growth and development in a harmonious and balanced social environment. This is the implementation of Law Number 1 of 2016 concerning Child Protection, this law is the second amendment of Law 23 of 2002. Online prostitution has often occurred, many victims are children and women. In the Child Protection Act, provisions concerning the protection of child victims of online prostitution have been regulated. However, in practice the regulations made have not been implemented effectively in the community. So it needs a lot of improvement in terms of implementation. After that, it can be seen from the legal consequences for child victims of child prostitution, namely in the form of special protection that is tried through supervision, protection, deterrence, treatment, and rehabilitation efforts. However, protection in the form of reintegration or the process of reintegration to parents and residents is also needed to help them through the recovery process properly.Keywords: children; protection and online prostitutionAbstrakAnak merupakan agent of change yang dimana anak harus dibina dan dilindungi tumbuh kembangnya secara fisik dan mental dalam lingkungan sosial yang selaras dan seimbang. Hal ini merupakan implementasi dari Undang-Undang Nomor 1 Tahun 2016 Tentang Perlindungan Anak undang-undang ini merupakan perubahan kedua dari Undang-Undang 23 Tahun 2002. Prostitusi Online sudah sering terjadi, banyak sekali korban dari kalangan anak dan perempuan. Dalam Undang-Undang perlindungan Anak memang sudah diatur ketentuan yang menyangkut perlindungan kepada anak korban dari Prostitusi Online. Namum dalam prakteknya peraturan yang dibuat belum diterapkan secara efektif di dalam masyarakat. maka dibutuhkan banyak sekali perbaikan dalam segi pelaksanaanya. Setelah itu bisa dilihat dari akibat hukumnya untuk anak korban prostitusi anak yakni berbentuk proteksi spesial yang dicoba lewat upaya pengawasan, proteksi, penangkalan, perawatan, serta rehabilitasi. Tetapi, proteksi berbentuk reintegrasi ataupun proses penyatuan kembali kepada orang tua serta warga pula diperlukan guna membantunya lewat proses pemulihan dengan baik.